2017
DOI: 10.1002/jbm.b.33909
|View full text |Cite
|
Sign up to set email alerts
|

Control of weft yarn or density improves biocompatibility of PET small diameter artificial blood vessels

Abstract: Polyethylene glycol terephthalate (PET) fabrics with woven structures have proved to be quite effective for use on large diameter artificial blood vessels. However, their use within small-diameter artificial blood vessels has been associated with poor long-term patency, a problem resulting from slow endothelialization on PET and an over hyperplasia of smooth muscle cells. Previous research from our laboratory has revealed that ICAM-1 can be used as a marker to investigate cell adhesion, an effect which was clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…With an increase in the culture time, gaps between fibers were filled with extracellular matrix (b in Figure ). It indicated that fibers provided an adhesion platform for ECs at the beginning . However, cells preferred to migrate to places with more nutrition like yarn gaps, which nutrition can permeate through.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an increase in the culture time, gaps between fibers were filled with extracellular matrix (b in Figure ). It indicated that fibers provided an adhesion platform for ECs at the beginning . However, cells preferred to migrate to places with more nutrition like yarn gaps, which nutrition can permeate through.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that fibers provided an adhesion platform for ECs at the beginning. 29 However, cells preferred to migrate to places with more nutrition like yarn gaps, which nutrition can permeate through. For stent-grafts modified with PDA-NP, ECs tended to stick and grow on PDA-NP (c in Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…The designed warp density was 850/10 cm and the weft density was 700/10 cm. Fabrics were washed three times (30 min each) with use of an ultrasonic cleaner and dried . Based upon previous results, fabrics were subjected to Ar 2 low temperature plasma treatment under varying conditions as summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were treated with 4% paraformaldehyde for 2 h followed by 4',6‐diamidino‐2‐phenylindole (DAPI), and Tetramethylrhodamine (TRITC) was used to stain the cells . Confocal laser scanning microscopy was used to observe adhesion of cells to the material surface after being subjected to dynamic culture.…”
Section: Methodsmentioning
confidence: 99%
“…Polyesters have been used for decades in a broad range of applications including films, fibers, and moldable engineering parts, and have recently received much attention as biodegradable and biocompatible polymers. [1][2][3][4][5][6][7][8][9] General synthetic methods for polyester include ring-opening polymerization of lactones and polycondensation of diol and dicarboxylic acid derivatives. In particular, the latter method can afford a wide variety of polyesters by changing the combination of the two monomers.…”
Section: Introductionmentioning
confidence: 99%